Growth faltering and recovery in children aged 1-8 years in four low- and middle-income countries: Young Lives - Lundeen, E; Behrman, J; Crookston, B; Dearden, K; Engle, P; Georgiadis, A; Penny, M; Stein, A; Consequen, Y (Cambridge University Press, 2013)
Objective: We characterized post-infancy child growth patterns and determined the incidence of becoming stunted and of recovery from stunting. Design: Data came from Young Lives, a longitudinal study of childhood poverty in four low- and middle-income countries. Setting: We analysed length/height measurements for children at ages 1, 5 and 8 years. Subjects: Children (n 7171) in Ethiopia, India, Peru and Vietnam. Results: Mean height-for-age Z-score (HAZ) at age 1 year ranged from -1.51 (Ethiopia) to -1.08 (Vietnam). From age 1 to 5 years, mean HAZ increased by 0.27 in Ethiopia (P < 0.001) and decreased among the other cohorts (range: -0.19 (Peru) to -0.32 (India); all P < 0.001). From 5 to 8 years, mean HAZ increased in all cohorts (range: 0.19 (India) to 0.38 (Peru); all P < 0.001). Prevalence of stunting (HAZ<-2.0) at 1 year ranged from 21 % (Vietnam) to 46 % (Ethiopia). From age 1 to 5 years, stunting prevalence decreased by 15.1 percentage points in Ethiopia (P < 0.001) and increased in the other cohorts (range: 3.0 percentage points (Vietnam) to 5.3 percentage points (India); all P ≤ 0.001). From 5 to 8 years, stunting prevalence decreased in all cohorts (range: 5.0 percentage points (Vietnam) to 12.7 percentage points (Peru); all P < 0.001). The incidence of becoming stunted between ages 1 to 5 years ranged from 11 % (Vietnam) to 22 % (India); between ages 5 to 8 years, it ranged from 3 % (Peru) to 6 % (India and Ethiopia). The incidence of recovery from stunting between ages 1 and 5 years ranged from 27 % (Vietnam) to 53 % (Ethiopia); between ages 5 and 8 years, it ranged from 30 % (India) to 47 % (Ethiopia). Conclusions: We found substantial recovery from early stunting among children in four low- and middle-income countries.